Free Lunch : easily digestible economics - Smith, David (London, 2009)
'There's no such thing as a free lunch' is the one phrase everyone has heard from economics. But why not? Never? What does economics tell us about the price of lunch - and everything else in the world? This is the perfect introduction to economics. It is not some dreary textbook, but an explanation of how economics works and how it can help to solve all sorts of interesting problems. Written for the lay reader, this book makes the economics pages of the newspaper intelligible, the financial pages interesting and answers questions all of us worry about, like how can house prices carry on rising so much? Is there no limit to the increase in their prices? Set out like a good lunch-time conversation, the book follows the course of a meal, with starters (the introduction), main course and then the discussion which one always has at the end of a good meal. And along the way there are a few guest speakers (Adam Smith, Karl Marx and John Maynard Keynes) who make appearances to enliven the meal and entertain and inform us, the diners. This is a clever, completely original and witty introduction to economics. It costs less than even the cheapest meal and is far more satisfying than even the most gourmet banquet.
Keywords: Economics